Direct Synthesis of Highly Crystalline ZSM-5 from Indonesian Kaolin - Hartati Hartati; Alfa Akustia Widati; Tanti Kartika Dewi; Didik Prasetyoko (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
Direct synthesis of ZSM-5 from Indonesian kaolin without calcination for the formation of metakaolin was done through the addition of an alkaline solution (sodium fluoride and sodium hydroxide) and the fusion using sodium hydroxide. Crystallization was conducted through hydrothermal method at 80 °C for four days. XRD diffractogram and FTIR spectra showed that the addition of sodium fluoride solution in the ratio Si/Al = 100 could produce highly crystalline ZSM-5, whereas the use of a sodium hydroxide solution and fusion process did not produce the crystalline ZSM-5.